2021
DOI: 10.3390/diagnostics11030445
|View full text |Cite
|
Sign up to set email alerts
|

Twin-to-Twin Transfusion Syndrome: Diagnostic Imaging and Its Role in Staving Off Malpractice Charges and Litigation

Abstract: The study aims to expound upon the imaging-based diagnostic methodologies aimed at identifying twin-to-twin transfusion syndrome (TTTS), a serious, somewhat rare prenatal condition that takes place in pregnancies where identical twins, or other multiples, share a placenta (monochorionic placenta), highlighting how medico-legal outcomes can be affected by provable compliance with consolidated diagnostic guidelines or best practices. It is of utmost importance to produce a prompt identification of TTTS instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The sonographic manifestations usually may be noted as early as 16 weeks of gestation, but they can appear in the third trimester as well. TTTS manifestations are rare after 28 weeks of gestation (Zaami et al, 2021). Despite the hypervolemia, vascular resistance in the recipient twin is increased.…”
Section: Clinical Manifestations Of Tttsmentioning
confidence: 99%
“…The sonographic manifestations usually may be noted as early as 16 weeks of gestation, but they can appear in the third trimester as well. TTTS manifestations are rare after 28 weeks of gestation (Zaami et al, 2021). Despite the hypervolemia, vascular resistance in the recipient twin is increased.…”
Section: Clinical Manifestations Of Tttsmentioning
confidence: 99%
“…4 In this regard, current guidelines strongly recommend serial sonography beginning in the first trimester and every 2 weeks from 16 weeks of gestation until 26 weeks as screening in monochorionic diamniotic twin pregnancies for the early detection of TTTS. 5,6 Ultrasound is the gold standard tool for the early detection of TTTS by tracking volume overload and polyuria followed by polyhydramnios in one twin and, paradoxically, oliguria followed by oligohydramnios in another twin. 7 For staging the severity of this phenomenon, the assessment of arterial and venous Doppler patterns along with bladder filling is very helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound examination serves as a routine method for predicting sIUGR. Previous studies have shown that the evaluation of utero-placental perfusion indices, including umbilical artery and middle cerebral artery velocimetry using Doppler ultrasound, have good efficacy for sIUGR prediction (9)(10)(11)(12)(13)(14). Additionally, magnetic resonance imaging (MRI) of placental invasion has recently become part of clinical practice (15); however, the major disadvantages of MRI include expensive devices and relatively complex techniques.…”
Section: Introductionmentioning
confidence: 99%